Plastome evolution in the genus Sium (Apiaceae, Oenantheae) inferred from phylogenomic and comparative analyses - Jing Zhou; Junmei Niu; Xinyue Wang; Jiarui Yue; Shilin Zhou; Zhenwen Liu (BMC Plant Biology, 2023)
Abstract Background Sium L. (Apiaceae) is a small genus distributed primarily in Eurasia, with one species also occurring in North America. Recently, its circumscription has been revised to include 10 species, however, the phylogenetic relationships within its two inclusive clades were poorly supported or collapsed in previous studies based on nuclear ribosomal DNA ITS or cpDNA sequences. To identify molecular markers suitable for future intraspecific phylogeographic and population genetic studies, and to evaluate the efficacy of plastome in resolving the phylogenetic relationships of the genus, the complete chloroplast (cp) genomes of six Sium species were sequenced. Results The Sium plastomes exhibited typical quadripartite structures of Apiaceae and most other higher plant plastid DNAs, and were relatively conserved in their size (153,029–155,006 bp), gene arrangement and content (with 114 unique genes). A total of 61–67 SSRs, along with 12 highly divergent regions (trnQ, trnG-atpA, trnE-trnT, rps4-trnT, accD-psbI, rpl16, ycf1-ndhF, ndhF-rpl32, rpl32-trnL, ndhE-ndhG, ycf1a and ycf1b) were discovered in the plastomes. No significant IR length variation was detected showing that plastome evolution was conserved within this genus. Phylogenomic analysis based on whole chloroplast genome sequences produced a highly resolved phylogenetic tree, in which the monophyly of Sium, as well as the sister relationship of its two inclusive clades were strongly supported. Conclusions The plastome sequences could greatly improve phylogenetic resolution, and will provide genomic resources and potential markers useful for future studies of the genus.